Sensitivity Assessment. Localization of Road Transport Infrastructures in the Province of Lucca - Luisa Santini; Serena Pecori (TeMA: Journal of Land Use, Mobility and Environment, 2014)
The work, result of a research carried out in collaboration with the Chamber of Commerce of Lucca, aims to implement a tool for the evaluation of positive and negative effects arising by the “widening” or “new construction” of road transport infrastructures in the territory. In particular, with respect to the impacts generated by the project actions relating to the construction or widening of roads, the research has produced several sensitivity maps of the studied area and a graphical interface, accessible on the Internet and user friendly, allowing the synthetic evaluation of the impacts and the comparison of different scenarios The implemented methodology, through the use of advanced tools for data management and processing and for impacts quantification and assessment, has allowed us to define a very detailed database related to all components of study area, both natural and anthropic, and to build a "synthetic sensitivity index", obtained from the combination of thematic information about each component and from the relationships that involve each others. It’s therefore to consider an indispensable support tool for planners and evaluators (eg. SEA procedures), but also for others users (eg organizations representing businesses, consumer associations, etc.). In fact it allows to acquire a deep knowledge of the area (environmental and economic resources), to verify the sensitivity of each part of the area with respect to a series of project actions concerning both the construction of new roads that the widening of the existing ones and finally to evaluate different localization scenarios for the same type of project or different impact scenarios for the same localization.